Effect of Active Detergent Ingredients on Successful Fertilization and Embryo Development of Sea urchins Tripneustes gratilla (Linnaeus, 1758) - Molle, Aprilia Paskarani; Marhendra, Agung Pramana Warih; Sri Rahayu (The Journal of Experimental Life Science, 2022)
The success of fertilization and development of sea urchin embryos Tripneustes gratilla can be used as a bioindicator of the water quality against the accumulation of pollutants. One of the contaminants that are often used is detergent with an active ingredient in the form of LAS. The purpose of this study was to analyze the effect of LAS on the success of fertilization and development of sea urchin embryos. This research was conducted in the Zoology Laboratory, Pattimura University, Ambon. Tripneustes gratilla were treated with exposure to the active ingredient LAS with a concentration of 0.0; 0.5; 1, and 2 mg.L-1. The parameter used to assess the success of fertilization is the formation of membrane fertilization. Parameters of embryo development are the division of 2, 4 , 8 , 16 , and 32 cells to form a morula, blastula, and hatching blastula. The results showed that the active ingredient of detergent LAS with a concentration of 0.5 mg.L-1 caused delays in the process of fertilization and embryo development. Meanwhile, the active ingredient LAS with concentrations of 1 and 2 mg.L-1 caused failure in the fertilization process and the embryonic development process of T. gratilla. Keywords: Detergent, embryo, fertilization, Tripneustes gratilla.